Wheat yield and grain-filling characteristics due to cultivar replacement in the Haihe Plain in China - Zhang, Xuecheng; Liu, Xiaoli; Wang, Li; Zhao, Qiancheng; Yu, Yang; Du, Ruirui; Xu, Yadong; Zhen, Wenchao; Wang, Yandong (Frontiers in Plant Science, 2024)
The Haihe Plain plays an important role in wheat production and food security in China and has experienced continuous cultivar replacement since the 1950s. This study assessed the evolution of the yield and grain-filling characteristics of the main winter wheat cultivars in the Haihe Plain over the last seven decades (1950s to date). Cultivar characterization indicated that the increase in yield was negatively affected by spike number and positively affected by the number of kernels per spike before the 2000s and kernel weight after the 2000s. Field trials were conducted across two ecological zones over two consecutive wheat-growing seasons. The results showed that genetic gains in grain yield, spike number, and kernel weight during 1955 to 2021 were 0.629%, 0.574%, and 0.332% yr -1 on a relative basis or 39.12 kg ha -1 , 24.35 thousand hm -2 , and 0.15 g yr -1 on an absolute basis, respectively. However, the increase in the kernel number per spike was not significant. Moreover, cultivar replacement explained 25.6, 12.8, and 37.5% of the total variance in grain yield, spike number, and kernel weight, respectively. In summary, during the initial grain-filling stage, wheat cultivar replacement led to the shortening of grain-filling duration and rapid grain-filling rate. However, a longer active grain-filling duration was produced by prolonged durations of rapid and late grain-filling. Additionally, the experimental year had a greater effect on the kernel number, which explained 53.2% of the total variance. Ultimately, modern wheat cultivars had a greater kernel weight. Although the increase in kernel weight has affected grain yield during cultivar replacements in the Haihe Plain, the potential for further yield increase through kernel weight enhancement alone is limited. Consequently, future breeding efforts and cultivation practices should focus on improving spike traits and canopy architecture to enhance productivity.